Pelatihan Teknik Cetak Tinggi dengan Format Mini Sebagai Hiasan di Café-Café Kekinian Pada Komunitas Grafis Makmur Sukoharjo - Sigit Purnomo Adi; Pande Made Sukerta; Martinus Dwi Marianto; Sri Hadi; Ariesa Pandanwangi (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
The proliferation of contemporary cafes in the Surakarta area and its surroundings has added to the increasing wheel of the economy. It is recognized that during the Covid 19 pandemic these efforts were somewhat dimmed, but after or after the Covid 19 pandemic, these efforts continued to increase. Contemporary cafe businesses, especially those that open coffee shops, mostly require something artistic, it can be in the form of decoration, appearance in arranging the room to other things. Decorations or cool language, aesthetic elements are needed to make these cafes more attractive to visitors, especially young people. Young people or children today need places to gather or hang out as well as places for selvi or making stories. Seeing this very promising business opportunity makes the author quite intrigued by this problem. Business opportunities, especially those engaged in making aesthetic elements on the walls of contemporary cafes. Based on the experience gained by the author as a graphic artist, it encourages the author to find suitable partners to be trained in the creation of graphic art works in the form of aesthetic elements, especially those using high and mini-sized printing techniques. The author finally chose the Makmur Graphic Community. This community is a community engaged in graphic studios, exhibition venues and also a place for graphic art work. The purpose of this PKM is to train and assist the Makmoer Graphic Community so that they can produce high-tech graphic art products in a mini format, as an aesthetic element in contemporary cafes in the Surakarta area and its surroundings. The choice of the Makmur Graphic Community as a partner is because this community is inhabited by very young members, besides that this community is already very present in the graphic arts arena, especially in the Surakarta area and its surroundings. Many events have been held both online and offline, it's just that this community has shortcomings, especially in the products produced. For the methodology, Asset Based Community Development (ABCD). The impact is clear that the Makmur Graphic Community is now not only able to produce works of graphic art as a medium of expression, but can also produce decorative works or aesthetic elements. The second clearly produces a significant impact in the economy because the demand for these crafts from time to time has increased. And this is very supportive of the theme of this national seminar, namely the role of universities in community empowerment in supporting progress after the Covid 19 pandemic.